Dlaczego sesja KMDD® jest „szyta na miarę” dla naszego mózgu? Stymulacja kompetencji moralnej z perspektywy neuropsychologicznej - Steć, Małgorzata (Filozofia Publiczna i Edukacja Demokratyczna, 2017)
Fostering moral competence with KMDD® may give the best results thanks to be suitable for our brain and its processes. Neuropsychological research shows importance of fostering moral competence with KMDD® for dlPFC and vmPFC cooperation. It should be taken into account that brain learns moral competence due to neuroplasticity and e.g. changes in the attention processes and high moral competence makes decisions more adequate and more quick. Not „only” cognition and not „only” emotions plays role in moral processing. Research shows obvious cooperation between those levels of neuronal processing. The article aims to show the brain areas which are most important for moral decision making and recent research findings on the KMDD® impact on brain functioning. What is most important this article is a kind of a try to answer the question: why KMDD® is the best method fostering moral competence according to neuropsychology.